The productivity of Sudan grass samples of various geographical origin - N. A. Kovtunova; E. A. Shishova; A. E. Romanyukin; V. V. Kovtunov; N. N. Sukhenko (Зерновое хозяйство России)
The productivity of Sudan grass samples of various geographical origin The experiments have been carried out in the FSBSI “Agricultural Research Center “Donskoy” (Rostov region) in 2016-2017. 160 varieties and lines, developed by the FSBSI “ARC “Donskoy”, the FRC “ARIGC after N. I. Vavilov” and other research institutions have been used as the objects of study. The samples received from China and Azerbaijan with the median of 1700-1850 g/m2 turned to be the most productive. The samples “К-187” (3952 g/m2), “К-62” (4020 g/m2), “К-236” (4100 g/m2), “Chernoplenchataya 10” (4930 g/m2), “Chernoplenchataya 11” (4845 g/m2) significantly surpassed the standard variety “Aleksandrina”. The correlation analysis shows that the productivity of green chop is assessed by the duration of the period of one cutting (r = 0.48 ± 0.00001), plant height (0.58 ± 0.002), width (0.53 ± 0.001) and leaf square (0.57 ± 0.001).